The incomplete circle of Willis is associated with vulnerable intracranial plaque features and acute ischemic stroke - Huiying Wang; Lianfang Shen; Chenxi Zhao; Song Liu; Gemuer Wu; Huapeng Wang; Beini Wang; Jinxia Zhu; Jixiang Du; Zhongying Gong; Chao Chai; Shuang Xia (Journal of Cardiovascular Magnetic Resonance, 2023)
Abstract Background The circle of Willis (CoW) plays a significant role in intracranial atherosclerosis (ICAS). This study investigated the relationship between different types of CoW, atherosclerosis plaque features, and acute ischemic stroke (AIS). Methods We investigated 97 participants with AIS or transient ischemic attacks (TIA) underwent pre- and post-contrast 3T vessel wall cardiovascular magnetic resonance within 7 days of the onset of symptoms. The culprit plaque characteristics (including enhancement grade, enhancement ratio, high signal in T1, irregularity of plaque surface, and normalized wall index), and vessel remodeling (including arterial remodeling ratio and positive remodeling) for lesions were evaluated. The anatomic structures of the anterior and the posterior sections of the CoW (A-CoW and P-CoW) were also evaluated. The plaque features were compared among them. The plaque features were also compared between AIS and TIA patients. Finally, univariate and multivariate regression analysis was performed to evaluate the independent risk factors for AIS. Result Patients with incomplete A-CoW showed a higher plaque enhancement ratio (P = 0.002), enhancement grade (P = 0.01), and normalized wall index (NWI) (P = 0.018) compared with the patients with complete A-CoW. A higher proportion of patients with incomplete symptomatic P-CoW demonstrated more culprit plaques with high T1 signals (HT1S) compared with those with complete P-CoW (P = 0.013). Incomplete A-CoW was associated with a higher enhancement grade of the culprit plaques [odds ratio (OR):3.84; 95% CI: 1.36–10.88, P = 0.011], after adjusting for clinical risk factors such as age, sex, smoking, hypertension, hyperlipemia, and diabetes mellitus. Incomplete symptomatic P-CoW was associated with a higher probability of HT1S (OR:3.88; 95% CI: 1.12–13.47, P = 0.033), after adjusting for clinical risk factors such as age, sex, smoking, hypertension, hyperlipemia, and diabetes mellitus. Furthermore, an irregularity of the plaque surface (OR: 6.24; 95% CI: 2.25–17.37, P < 0.001), and incomplete symptomatic P-CoW (OR: 8.03, 95% CI: 2.43–26.55, P = 0.001) were independently associated with AIS. Conclusions This study demonstrated that incomplete A-CoW was associated with enhancement grade of the culprit plaque, and incomplete symptomatic side P-CoW was associated with the presence of HT1S of culprit plaque. Furthermore, an irregularity of plaque surface and incomplete symptomatic side P-CoW were associated with AIS.